Research on the Influence Mechanism of Global Enterprises' Return Investment on Enterprise Performance - Zhang, Gaohan (International Journal of Global Economics and Management, 2023)
This study focuses on the mechanisms by which global firms' return investment affects performance, using resource dependence, opportunity cost and capital structure as the main theoretical perspectives. The resource dependence perspective suggests that return investment is a strategy for firms to acquire and protect resources, and to reduce their dependence on external markets by repatriating capital, technology, and brand resources. This process may be achieved through internal resource reallocation, organizational culture adjustment and strategic innovation, which profoundly affects firm performance. Opportunity cost theory emphasizes the choice and abandonment in the return investment decision, and firms need to weigh the substitutability and long-term competitiveness of different opportunities, revealing the mechanisms of strategic choices, cultural changes, and business model innovations that may be involved in return investment, thus affecting long-term performance. Capital structure theory provides a framework for understanding the internal and external impacts of return investment on firms. The choice of capital structure directly affects a firm's competitive position in the domestic market, financial flexibility, and long-term value creation. Repatriation investments may adjust the capital structure through debt and equity adjustments to fit the needs of the home market. The capital structure perspective provides insights into the mechanisms by which return investment affects firms' financing decisions, resource allocation efficiency, and financial flexibility. At the industry and market level, return investment may lead to intra-organizational changes and market-level effects. Capital repatriation may drive firms to engage in industry consolidation, reposition themselves competitively in the market, and restructure supply and value chains. Through these mechanisms, firms will reshape their competitive position in their home markets, generate market strategies and competitive advantages that differ from those in international markets, stimulate innovation and development in their home markets, and influence the evolution of the industry as a whole and changes in the market landscape.